It's kina hard da' cry: art and writings by adults incarcerated (Liberatory stories and rebel voices for abolition, 2025)
"It's Kina Hard Da' Cry: Art and Writing by Adults Incarcerated by Save the Kids (STK) is one of the only books with a collection of writing and art by justice impacted people throughout the U.S. This powerful ground-breaking critical thought provoking chilling book is a must read for anyone that wants to know the heart and mind of those behind the walls of prison. This book is a yell to listen to those incarcerated. This book is dedicated to providing a space and place for the voices of incarcerated adults to critically express their experiences related to the criminal justice system, school system, and their community"--